Knowledge and practices of primary eye care among non-ophthalmic nurses working in Kweneng East District Clinics, Botswana. - Motswakadikgwa, Neo Ruth (Division of General Surgery, 2026)
Background: Primary eye care (PEC) is important in preventing and managing eye conditions, particularly in rural areas where access to specialized care is limited. Aim and Setting: The study aim was to assess the primary eye care knowledge and practices of non-ophthalmic nurses in Kweneng East District clinics, Botswana. Methodology: A descriptive cross-sectional study design, with quantitative methods of analysis was used. The study sample was selected using both systematic and convenience sampling methods. A self-administered questionnaire was developed and provided to 195 consenting non-ophthalmic nurses from 36 clinics. The completed questionnaires were collected, data captured and analyzed using both descriptive and inferential statistical methods. Results: 39.1% of all participants scored correct responses on knowledge of identification of common eye conditions. The overall proportion of correct management responses for all participants was 37.9%, while for correct PEC practices the proportion was 56.3%. The study found a significant relationship between professions (P=0.04), years of experience (P=0.03), and primary care training (P=0.05) and knowledge of primary eye care conditions. Conclusion The study found that knowledge, management, and practices of primary eye care was inadequate among non-ophthalmic nurses in the Kweneng East District. There is a need for continuous professional development, refresher training, and curriculum adjustments in nurses' education to enhance PEC services in the region. Contribution: The study will inform how to improve PEC services in the country.